2005
DOI: 10.1007/s11661-005-0326-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cold deformation on the kinetics of the β″ precipitates in an Al-Mg-Si alloy

Abstract: Kinetics of ␤Љ precipitation in an Al-0.55 pct Mg-1.1 wt pct Si (AA6022) in both deformed and undeformed conditions were investigated by means of differential scanning calorimetry (DSC). Transmission electron microscopy (TEM) analysis on predeformed samples was also performed to study the effect of deformation on ␤Љ precipitates. It was found that the introduction of dislocations changes the precipitate type from ␤Љ to ␤Ј and QЈ. Also the measured activation energy for precipitate formation in the case of pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
2
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 25 publications
1
32
2
1
Order By: Relevance
“…Nevertheless, a small Mg2Si peak is still observed after four passes. Panigrahi et al [23] reported that the formation of the Mg2Si phase after SPD could be explained by the accumulation of dislocations that may act as a shortcircuit path for solutes and atomic migration facilitating this precipitation. Furthermore, they added that the frictional heat induced on the sample caused a clustering of Mg and Si atoms with vacancies, leading to the formation of Mg2Si peak in the XRD pattern.…”
Section: X-ray Diffraction Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, a small Mg2Si peak is still observed after four passes. Panigrahi et al [23] reported that the formation of the Mg2Si phase after SPD could be explained by the accumulation of dislocations that may act as a shortcircuit path for solutes and atomic migration facilitating this precipitation. Furthermore, they added that the frictional heat induced on the sample caused a clustering of Mg and Si atoms with vacancies, leading to the formation of Mg2Si peak in the XRD pattern.…”
Section: X-ray Diffraction Analysismentioning
confidence: 99%
“…On the other hand, among the age hardenable aluminum alloys, the Al-Mg-Si system has been the object of extensive investigation considering its technological importance as the basis of the high strength aluminum alloys. The precipitation sequence usually proposed for this type of alloys is as follows [13,14]:…”
Section: Introductionmentioning
confidence: 99%
“…For Al-Mg-Si alloys, previous work revealed by DSC analysis that pre-straining accelerates precipitation because of decreased activation energy for the growth of precipitates. 8,9) Matsuda et al 10) reported that 5% pre-strain following pre-aged at 423 K for 60 ks improves bake-hardening response in under-aged condition and results in higher peak hardness at 473 K for an Al-0.37 mass%Mg-0.62 mass%Si alloy. Furthermore, Birol et al 11,12) reported that pre-straining shortly after solution heat treatment suppresses clustering behavior at room temperature, but results in the enhanced formation of the 00 phase during aging at 453 K. These suggest that the combined effect of pre-straining and pre-aging is quite useful, but still have room for investigation under various combinations of the amount of pre-strain and pre-aging temperature.…”
Section: )mentioning
confidence: 99%
“…It has been reported [27][28][29][30][31] that 10%-15% pre-deformation leads to formation of heterogeneous nucleation along dislocation lines. After artificial aging, different types of precipitates (except for β") form: a continuous decoration of the dislocation lines ("string-like" precipitates) together with discrete precipitation consisting mainly of B' [27][28][29][30], and together with (often disordered) Q' [11,12,31,32] if Cu is present in the Al-Mg-Si alloys. In the case of 0.5%-5% pre-deformation, β" is dominant at peak hardness condition, and this level of pre-deformation accelerates formation of β" due to decreased activation energy [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%